Implementation of Chatbot to Improve Service in Purchasing Batik - Arminta, Marilyn Jasmine; Nugroho, Agus Cahyo; Prasetya, FX. Hendra (SISFORMA, 2025)
The rise of e-commerce has significantly changed consumer purchasing behavior. For example, the purchase of culture-related goods such as batik is now also done online. Currently, batik sellers often rely on manual communication, such as short messages, to provide product and business information, which causes delays in response time and potential lost sales opportunities. In addition, batik sellers also often receive the same questions from customers, making it ineffective and inefficient in running their business. To overcome this problem, a chatbot named BatikBot was created in the form of a website. This chatbot aims to answer common questions that customers often ask to increase customer satisfaction and operational efficiency. The method used in the development of this chatbot is the waterfall method, which is modeled with a use case diagram, activity diagram, and sequence diagram. The development process uses Program O as a tool for making chatbots. The final result of this development is a website with a chatbot named BatikBot that is expected to not only improve the shopping experience for consumers but also support batik sellers in managing their business more effectively while contributing to the preservation of Indonesia's cultural heritage.